2006
DOI: 10.1161/01.atv.0000204350.44226.9a
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Reactions of Nitric Oxide, Nitrite, and Hemoglobin in Physiology and Therapeutics

Abstract: Abstract-The ability of oxyhemoglobin to inhibit nitric oxide (NO)-dependent activation of soluble guanylate cyclase and vasodilation provided some of the earliest experimental evidence that NO was the endothelium-derived relaxing factor (EDRF). The chemical behavior of this dioxygenation reaction, producing nearly diffusion limited and irreversible NO scavenging, presents a major paradox in vascular biology: The proximity of large amounts of oxyhemoglobin (10 mmol/L) to the endothelium should severely limit p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
204
0
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 264 publications
(219 citation statements)
references
References 119 publications
(142 reference statements)
1
204
0
7
Order By: Relevance
“…The more difficult challenge has been to inhibit the rate of NO scavenging without markedly altering the rates of O 2 uptake and release. The key reactions of NO with reduced Hb are shown in Figure 3A (69,99). Even if some free NO binds to deoxyHb, its ultimate fate will be irreversible dioxygenation to nitrate if any O 2 is present (45).…”
Section: Controlling O 2 Affinity and Nodmentioning
confidence: 99%
“…The more difficult challenge has been to inhibit the rate of NO scavenging without markedly altering the rates of O 2 uptake and release. The key reactions of NO with reduced Hb are shown in Figure 3A (69,99). Even if some free NO binds to deoxyHb, its ultimate fate will be irreversible dioxygenation to nitrate if any O 2 is present (45).…”
Section: Controlling O 2 Affinity and Nodmentioning
confidence: 99%
“…Our results invite a rethink about the role of hemoglobin in NO biology, because its oxygenated form is considered an NO scavenger under any condition. Several factors have been identified that explain why endothelial NO escapes scavenging by hemoglobin, 8,11,45,48,49 but those discussions did not consider the possibility that NO might be produced in RBCs themselves. The observation that NO formation can be detected in the vicinity of abundant oxyhemoglobin would seem to warrant a careful reassessment of this universally accepted paradigm.…”
Section: Is Red Cell Enos Of Relevance To Cardiovascular Disease?mentioning
confidence: 99%
“…In normal physiology, the reason that endothelial-derived NO is not scavenged to the extent predicted, based purely on kinetic calculations, is that red blood cell (RBC) encapsulated Hb in the blood reacts with NO much more slowly than does cell-free Hb [35][36][37][38][39][40][41][42][43][44][45]. Three mechanisms contribute to reduced NO scavenging by RBCs [46]. : (1) the rate of the reaction is largely limited by external diffusion of NO through the plasma to the surface of the RBC [44], especially due to the presence of a red cell free zone adjacent to the vessel walls where NO is made [37][38][39]; (2) NO diffusion is partially blocked by a physical barrier across the RBC membrane [40,43,47]; and (3) RBC-encapsulated Hb is efficiently compartmentalized in the lumen; it does not extravasate into the endothelium and interstitium [44,[48][49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…All three mechanisms are disrupted during intravascular hemolysis [46]. The increased ability of cell-free Hb to scavenge NO has been widely attributed to the hypertension, increased systemic and pulmonary vascular resistance, and morbidity and mortality associated with administration of hemoglobin-based oxygen carriers (HBOCs or "blood substitutes") [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67].…”
Section: Introductionmentioning
confidence: 99%